Filsafat dalam Kurikulum Pendidikan Islam - Gatot Kaca (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Philosophy in Islamic Education curriculum. The world of Islamic education in Indonesia in particular, and the Islamic world in general are still faced with various problems ranging from questions about the formulation of educational goals that are not in line with the demands of society, to the problems of teachers, methods, curriculum and so on. Efforts to overcome these problems are still being made with various efforts. Upgrading of teachers, training, education management personnel and others must be done, but education problems continue to emerge. Efforts to improve such educational conditions seem to need to be traced to the root of the problem which is based on philosophical thought. Philosophy of Islamic education in general will examine various problems contained in the field of education, ranging from vision and mission, educational objectives, fundamentals and principles of Islamic education, human concepts, teachers, students, curriculum, and methods to evaluation in education philosophically. In other words, this science will try to use the services of thought. The fact shows there are many Islamic education mecca that is not yet clear. Islamic education has not yet found its specific format and form in accordance with the religion of Islam. This is not only due to the many concepts of education offered by experts who are not yet clear of Islam, nor because there are not many Islamic education experts who design Islamic education carefully.